Lipoleiomyoma of Uterus with Coexisting Leiomyoma Showing Hyaline Change in a 60-Year-Old Female: A Rare Case Report: Lipoleiomyoma of the uterus with coexisting leiomyoma showing hyaline change in a 60-year-old female - Panwan, Jeffry; Aggarwal, Tanya; ., Kritika; Kaur, Kanwardeep (Indian Journal of Case Reports, 2026)
Lipoleiomyoma is a rare benign lipomatous variant of uterine leiomyoma composed of mature adipose tissue admixed with smooth muscle fibers. It is predominantly seen in peri- and postmenopausal women and may clinically and radiologically mimic malignant pelvic neoplasms. We report a case of a 60-year-old postmenopausal female who presented with lower abdominal discomfort. Ultrasonography revealed a bulky postmenopausal uterus with a large heteroechoic lesion in the uterine cavity suggestive of endometrial SOL. MRI pelvis demonstrated multiple submucosal leiomyomas with fatty degeneration and hemorrhagic changes. Total hysterectomy specimen on gross examination revealed two well-circumscribed intramural nodules with characteristic yellow-white whorled appearance. Histopathological examination showed one leiomyoma with extensive mature adipose tissue consistent with lipoleiomyoma and another leiomyoma with hyaline degeneration. Lipoleiomyoma is an uncommon benign uterine neoplasm and should be considered in the differential diagnosis of fat-containing pelvic masses in postmenopausal women.